Serial assessment of postoperative ventricular mechanics in young children with tetralogy of Fallot: Comparison of transannular patch and valve‐sparing repair. (15th April 2019) - Annavajjhala, Vidhya; Punn, Rajesh; Tacy, Theresa A.; Hanley, Frank L.; McElhinney, Doff B.
Abstract: Background: Little is known about the early time course of biventricular function and mechanics after tetralogy of Fallot (TOF) repair. We sought to evaluate and describe the evolution of the right ventricle (RV) after TOF repair in young infants and children using conventional echocardiographic parameters and global longitudinal strain (GLS). Methods: A retrospective review was performed of all patients with TOF and pulmonary stenosis who underwent repair from January 2002 to September 2015 and had at least 3 serial postsurgical echocardiograms spanning from infancy to early childhood (<8 years). Student's t test was performed to compare patients who underwent valve sparing (VS) versus transannular patch (TAP) repair. ANOVA was used to track measures of ventricular systolic function over time. Results: We analyzed 151 echocardiograms performed on 42 patients. Pulmonary regurgitation (PR, moderate or severe) and the RV to left ventricular (LV) basal dimension ratio were higher in TAP patients ( P < .04 at all‐time points). Along with a significant increase in RV basal diameter Z ‐score in the TAP group ( P < .001), there was an improvement in RV and LV GLS over time in both groups ( P < .001). The LV GLS at last follow‐up was lower in patients who underwent reoperation than those who did not ( P = .050). LV GLS at the last follow‐up echocardiogram was lower in patients with significant PR than those without ( P < .001). Conclusions: Ventricular function appeared improve over time from the initial postoperative period in TOF patients. TAP repair was associated with a progressively higher RV/LV ratio in young children. GLS and RV/LV basal diameter ratio may be useful when following young children after TOF repair. Further research is necessary to understand the trajectory of ventricular functional and volumetric changes in young children in order to provide the most effective lifetime management of patients with TOF.